تكنولوجيا المعلومات وتطبيقاتها في المكتبات الجامعية - ميدوني, ليلى (University of Eloued جامعة الوادي, 2022)
تعتبر المكتبة الجامعية مؤسسة أكاديمية تسعى لتوفير الحاجات المعلوماتية لفئة المستفيدين طلبة أساتذة باحثين. لاسيما في ظل التطور السريع والمستمر من انتاج التقنيات الحديثة وسرعة نقل المعلومة حيث بات من الضروري مواكبة هذه التغيرات لتقليص الفجوة مع المجتمعات الاخرى .حيث تبرز هذه الفجوة في مدى امتلاك المعلومات التي تعد مؤشر حقيقي لقيام تقدم الامم، كما تساهم المعلومات في نمو وتقدم الدول. و من جانب أخر فتكنولوجيا المعلومات تهدف إلى جمع المعلومات وتخزينها واسترجاعها وتناقلها وتستعرض هذه الدراسة ونتسأل عن أهمية ومهام المكتبات الجامعية وما مدى التغيرات التي أحدثتها تكنولوجيا المعلومات بالمكتبات الجامعية. حيث أصبح لتكنولوجيا المعلومات أهمية بالغة في توفير الخدمات المعلوماتية. نظرا لما تملكه من إمكانات وما توفره من رفع لفواصل بين المجتمعات .Abstract: The University Library is an academic institution that seeks to provide information needs for the beneficiaries' category. Especially with the rapid and continuous development of the production of modern technologies and the rapid transmission of information, it is necessary to keep pace with these changes to reduce the gap with other societies. This gap is highlighted in the extent of possession of information, which is a real indicator of the progress of the nations, where information contributes to the growth and progress of countries. On the other hand, IT aims to collect, store, retrieve and transmit information. We review this study and ask about the importance and functions of university libraries and the extent of the changes made by IT in university libraries. Information technology has thus become crucial to the provision of information services. in view of its potential and its enhancement of intercommoned divides
مقال